2017
DOI: 10.1186/s12872-017-0719-7
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural heparin bridging in patients receiving oral anticoagulation: a systematic review and meta-analysis

Abstract: BackgroundPeriprocedural heparin bridging therapy aims to reduce the risk of thromboembolic events in patients requiring an interruption in their anticoagulation therapy for the purpose of an elective procedure. The efficacy and safety of heparin bridging therapy has not been well established.ObjectivesTo compare through meta-analysis the effects of heparin bridging therapy on the risk of major bleeding and thromboembolic events of clinical significance among patients taking oral anticoagulants.MethodsWe searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…In this study, we critically selected relevant studies and conducted a rigorously scientific synthesis of research results. Prior meta‐analyses evaluating the risk and benefit of bridging anticoagulation are flawed with inclusions of few randomized trials and studies with no control arm, no separate analysis of three strategies (interrupted anticoagulation with bridging therapy, interrupted anticoagulation without bridging therapy and continuous oral anticoagulation), and no detailed assessment of study quality . We found that bridging anticoagulation was associated with higher bleeding risk and similar thromboembolic risk compared to non‐bridging strategy.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, we critically selected relevant studies and conducted a rigorously scientific synthesis of research results. Prior meta‐analyses evaluating the risk and benefit of bridging anticoagulation are flawed with inclusions of few randomized trials and studies with no control arm, no separate analysis of three strategies (interrupted anticoagulation with bridging therapy, interrupted anticoagulation without bridging therapy and continuous oral anticoagulation), and no detailed assessment of study quality . We found that bridging anticoagulation was associated with higher bleeding risk and similar thromboembolic risk compared to non‐bridging strategy.…”
Section: Discussionmentioning
confidence: 83%
“…[5657] In a recent meta-analysis of 25 studies ( n = 35,944), bridging therapy did not reduce thromboembolic events and actually led to increased risk of overall and major bleeding. [58] Thus, bridging therapy with LMWH seems to be efficacious only in patients at high risk of thrombosis.…”
Section: Indications Contraindications and Complications Of Flexiblmentioning
confidence: 99%
“…Here, bridging led significantly more often to bleeding events (odds ratio [OR]: relevant bleeding 3.23; OR minor bleeding 1.52). Between the two groups, no differences in thromboembolic events were observed [ 84 ].…”
Section: Literature Review On Bleeding Disorders In Dentistrymentioning
confidence: 99%